EVALUASI EFEKTIVITAS BUDAYA INOVASI PADA GEORGETTE TEXTILES BERDASARKAN SIX BUILDING BLOCKS OF AN INNOVATIVE CULTURE - Asrunputri, Aisyah Pia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
Innovation is imperative to be applied by the company in order to respond to the industrial dynamic and also to respond to market and consumers demand. With the right management of innovation and its practise will help the company to optimize the initiative strategy in order to respond to those changes that happen in the company. The author focuses this research to the evaluate the effectiveness of innovative culture at Georgette Textiles using Six Building Blocks of an Innovative Culture as the management evaluation tool that is suitable for this research.Â The method that is used in this research is qualitative method, which is in-depth interview with the marketing export specialist at Georgette Textiles. Based on the findings the company must emphasize on its company flexibility and adaptability through the creation of effective innovative culture to respond to the changes and to maximize the opportunities lie within the company.Â Key Words: Innovation, Industrial Dynamic, Georgette Textiles, Six Building Blocks of an Innovative Culture